Low expression of soluble human leukocyte antigen G in early gestation and subsequent placenta‐mediated complications of pregnancy. Issue 9 (10th July 2017) - Marozio, Luca; Garofalo, Anna; Berchialla, Paola; Tavella, Anna Maria; Salton, Loredana; Cavallo, Franco; Benedetto, Chiara
Abstract: Aim: Abnormal placentation is a common pathogenic mechanism of many placenta‐mediated complications of late pregnancy, including pre‐eclampsia, fetal growth restriction, stillbirth, and placental abruption. During successful placentation, the trophoblast (which is a semi‐allograft) is not rejected by decidual immune cells because of maternal immune tolerance, mainly induced by human leukocyte antigen G (HLA‐G). Deficient HLA‐G expression seems to be associated with the development of complications of pregnancy. The aim of this study was to determine whether low soluble HLA‐G (sHLA‐G) levels in maternal blood at the beginning of pregnancy may be associated with subsequent placenta‐mediated complications. Methods: For this retrospective case–control study, 117 cases of placenta‐mediated complications of pregnancy and 234 controls with uneventful pregnancy were selected. Plasma sHLA‐G levels were measured at 11–13 weeks' gestation by the enzyme‐linked immunosorbent assay method in blood samples previously obtained at first‐trimester prenatal screening for chromosomal fetal abnormalities. Results: Women who subsequently developed placenta‐mediated complications had significantly lower sHLA‐G levels at the beginning of pregnancy (median, 43.08 IU/mL) than controls (median, 49.10 IU/mL; P  = 0.008). An sHLA‐G level lower than 43.50 IU/mL at the end of the first trimester was associated with a twofold increased risk of developing a pregnancy complication (odds ratio, 1.82; 95% confidence interval, 1.22–2.73). The strongest association, although only moderately strong, was observed with severe pre‐eclampsia (odds ratio, 2.66; 95% confidence interval, 1.08–6.56). Conclusion: Placenta‐mediated complications of pregnancy may be associated with low sHLA‐G levels in the first trimester, suggesting a potential role of sHLA‐G in the early stages of placentation.